Green FDI: Encouraging carbon-neutral investment - Karl P. Sauvant; Matthew Stephenson; Yardenne Kagan (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2021)
The world needs more "Green FDI" that contributes to environmental objectives, including the reduction of greenhouse gas emissions. Goals have been set by countries and MNEs to reduce emissions. To support meeting these commitments–and encourage additional MNEs to reduce emissions–this Perspective suggests proactive policies that should be pursued.
Keywords: 330